2015
DOI: 10.1177/1535370215579013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thymoquinone treatment on the combined renal and pulmonary toxicity of cisplatin and diesel exhaust particles

Abstract: Particulate air pollution (PAP) exposure is associated with increased morbidity and mortality, particularly in patients with renal disease. However, there are only a few studies on the interaction between PAP and renal injury, and none on agents that may ameliorate it. We studied the interaction between cisplatin (CP) nephrotoxicity and a single exposure to diesel exhaust particle (DEP) in rats 24 h before sacrifice, and assessed the effect of co-treatment with the active ingredient in Nigella Sativa seed oil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
1
17
1
Order By: Relevance
“…Treatment with GA did not show significant ameliorative effect on the observed changes. In line with these findings, recent studies by Ali et al (2015) and Nemmar et al (2015) showed that repeated exposure to DP potentiated cisplatin-induced nephrotoxicity. Systolic blood pressure was increased, levels of nitric oxide were elevated and the renal tubular necrosis was aggravated.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Treatment with GA did not show significant ameliorative effect on the observed changes. In line with these findings, recent studies by Ali et al (2015) and Nemmar et al (2015) showed that repeated exposure to DP potentiated cisplatin-induced nephrotoxicity. Systolic blood pressure was increased, levels of nitric oxide were elevated and the renal tubular necrosis was aggravated.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, it has been suggested that there is a link between exposure to air pollution and cardiovascular disease in kidney transplant recipients (Spencer‐Hwang et al, ). Moreover, in vivo experimental studies have provided evidence that exposure to DP in the lung aggravates the renal, pulmonary, and systemic effects of cisplatin‐induced acute renal failure in rats (Nemmar et al, ; Nemmar et al, ; Ali et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al [61] studied the interaction between cisplatin (CP) nephrotoxicity and a single exposure to diesel exhaust particles and the concurrent treatment with TQ (20 mg/kg, orally) in rats. The results showed that several biochemical, physiological, and histopathological alterations contained decreased growth and Cr clearance and increased IL-6, plasma neutrophil gelatinase-associated lipocalin, C-reactive protein, urea and Cr concentrations, and urinary N-acetyl-b-D-glucosaminidase (NAG) activities induced by CP, and were significantly abrogated by TQ.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that several biochemical, physiological, and histopathological alterations contained decreased growth and Cr clearance and increased IL-6, plasma neutrophil gelatinase-associated lipocalin, C-reactive protein, urea and Cr concentrations, and urinary N-acetyl-b-D-glucosaminidase (NAG) activities induced by CP, and were significantly abrogated by TQ. Also, TQ significantly resolved potentiated indices of oxidative injuries in the kidney tissues, and induced renal tubular necrosis induced by CP and diesel exhaust particles [61]. …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Budinger et al (2011) suggested that IL-6 is significantly associated with PM-induced thrombogenic effects independent of other inflammatory markers [ 61 ]. Two studies have been published examining the effect of anti-inflammatory agents on thrombogenic factors in mice following exposure to DEP (15–30 μg) [ 66 , 67 ]. Both studies demonstrated a critical role for inflammation in mediating DEP-induced thrombotic effects [ 66 , 67 ].…”
Section: In Vivo Studies In Animalsmentioning
confidence: 99%